Hydrogen permeation in a palladium membrane tube: Impacts of outlet and vacuum degree. (12th December 2022) - Chen, Wei-Hsin; Chen, Zih-Yu; Lim, Steven; Park, Young-Kwon; Show, Pau-Loke
Abstract: Palladium (Pd) membranes are a crucial device for separating hydrogen and are usually operated at normal pressure on the permeate side with a single outlet. Instead of these common operating conditions, the difference between using a double outlet and a single outlet is studied. Four different vacuum degrees (15–60 kPa) are applied on the permeate side, and the results are compared with the non-vacuum operations. Situations under the vacuum and the effects of temperatures (300–400 °C) on H2 permeation are discussed. Finally, the influences of different feed gas mixtures (H2 /N2, H2 /CO2, and H2 /CO) on the Pd membrane performance are investigated. The results show that there is no difference in H2 permeation impact the single outlet and the double outlet on the permeate side. When a vacuum is imposed on the permeate side, the H2 permeation rate and H2 recovery are efficiently intensified, that is, when the pressure difference is 9 atm, they increase from 73.21 to 84.51% and from 0.0035378 to 0.0040808 mol∙s −1, respectively. Moreover, the H2 recovery can be improved to up to 68.44% under a vacuum degree of 60 kPa. At a given Reynolds number, an increase in temperature increases the H2 permeation rate but lowers its recovery, stemming from more H2 in the feed gas. This study also investigates the feed gas of H2 /N2 under a vacuum to provide a useful insight into H2 production and separation from ammonia, and the results are compared with two different feed gases of H2 /CO2 and H2 /CO mixtures. The results suggest that the impurities (i.e., N2, CO2, and CO) have a negative influence on the Pd membrane, which causes the H2 permeation rate to decrease, and the effect of N2 is the least significant compared to the other two. Graphical abstract: Image 1 Highlights: The impact of the number of outlets on the H2 permeation rate and recovery is very small. Imposing a vacuum on the permeate side can efficiently enhance H2 permeation. The higher the temperature and vacuum degree, the better the improvement. The H2 permeability rises with increasing temperature but H2 recovery decreases. Impurities CO2 and CO have a more negative effect on H2 permeation compared to N2 .